2004
DOI: 10.1055/s-2004-826039
|View full text |Cite
|
Sign up to set email alerts
|

Chromoendoscopy Using Indigo Carmine Dye Spraying with Magnifying Observation Is the Most Reliable Method for Differential Diagnosis between Non-Neoplastic and Neoplastic Colorectal Lesions: A Prospective Study

Abstract: Chromoendoscopy with magnification is the most reliable method for determining whether a colorectal lesion is non-neoplastic or neoplastic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
164
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(173 citation statements)
references
References 6 publications
4
164
2
3
Order By: Relevance
“…The diagnostic accuracy with the different techniques in our study was lower than in some other series [2,5,[13][14][15][16] . Possible explanations for such differences are that some series included larger polyps, which are probably easier to diagnose [5,[13][14][15] , or that diagnosis was estimated with a live video-endoscopy image and not with stored [2,13] , which could enable a more exact diagnosis.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…The diagnostic accuracy with the different techniques in our study was lower than in some other series [2,5,[13][14][15][16] . Possible explanations for such differences are that some series included larger polyps, which are probably easier to diagnose [5,[13][14][15] , or that diagnosis was estimated with a live video-endoscopy image and not with stored [2,13] , which could enable a more exact diagnosis.…”
Section: Discussioncontrasting
confidence: 50%
“…Possible explanations for such differences are that some series included larger polyps, which are probably easier to diagnose [5,[13][14][15] , or that diagnosis was estimated with a live video-endoscopy image and not with stored [2,13] , which could enable a more exact diagnosis. Some series used absorptive stains, which can be more accurate [13,14] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, chromoendoscopy with dye-spraying, which provides a more detailed visualization of the mucosa by enhancing its morphology, was developed to improve upon the accuracy afforded by conventional endoscopy (7)(8)(9). The authors of the present study (10,11) and other studies (12)(13)(14)(15)(16) have previously demonstrated that this imaging technique facilitates the detection of early-stage neoplastic lesions in UC.…”
Section: Introductionmentioning
confidence: 85%